(untitled) (Dissertare, 2018)
Marianismo is a psychosocial and cultural phenomenon that started in Spanish America when the Virgin Mary, at the end of the 15th century and the beginning of the 16th century, became part of the identity of those peoples that were born or founded. From the socio-cultural standpoint, it is interesting to analyze this category present in Spanish-speaking peoples, as a religious phenomenon, within popular culture and to establish the relationship between devotion to Mary and Venezuelan popular culture in the 20th century, given the various Marian invocations in the country. The essay is approached from the perspective of the descriptive and retrospective method, in search of an approach to the historical process in which Marianismo and popular culture coexist and interweave. To this end, the work was based on the documentary review of the literature on the two thematic elements addressed, as a sustainable basis of the historical fact, to understand the social and cultural reality. It is concluded that Marianismo, as a socio-cultural phenomenon, retains an anthropological, spiritual and ecclesiastical vitality, forming part of the social reality of the nation, that is to say, it has validity in the daily life of Christian identity, in the practice of faith and in the cultural history of the country in the twentieth century, because religiosity, Marianismo and popular culture are connected to build a network of social, cultural and religious behaviors, which are part of the identity of the people.